Do Electric Vehicles Mitigate Urban Heat? The Case of a Tropical City - Mussetti, Gianluca; Davin, Edouard L.; Schwaab, Jonas; Acero, Juan A.; Ivanchev, Jordan; Singh, Vivek Kumar; Jin, Luxi; Seneviratne, Sonia I. (Frontiers in Environmental Science, 2022)
On top of their well known positive impact on air quality and CO2 emissions, electric vehicles generate less exhaust heat compared to traditional vehicles thanks to their high engine efficiency. As such, electric vehicles have the potential to mitigate the excessive heat in urban areas - a problem which has been exacerbated due to urbanisation and climate change. Still, the heat mitigation potential of electric vehicles has not been fully understood. Here, we combine high-resolution traffic heat emission inventories with an urban climate model to simulate the impact of the fleet electrification to the near-surface air temperature in the tropical city of Singapore. We show that a full replacement of traditional internal combustion engine vehicles with electric vehicles reduces the near-surface air temperature by up to 0.6 °C. The heat mitigation potential is highest during the morning traffic peak and over areas with the largest traffic density. Interestingly, the reduction in exhaust heat emissions due to the fleet electrification during the evening traffic peak hardly leads to a reduction of near-surface air-temperatures, which is attributed to the different atmospheric conditions during morning and evening. This study presents a new quantification of the city-wide impact of electric vehicles on the air temperature in a tropical urban area. The results may support policy-makers toward designing holistic solutions to address the challenge of climate change adaptation and mitigation in cities.